2008
DOI: 10.1111/j.1479-828x.2008.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting caesarean operative time and the effect of operative time on pregnancy outcomes

Abstract: Operative time is shortened by age < 18 and delivery for fetal labor intolerance, lengthened by age > 35, BMI > 30, prior caesarean, uterine incision, operating surgeon inexperience and accompanying sterilisation. Increased operative time was linked with an increased blood loss, low five-minute Apgar scores and umbilical arterial pH < 7.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 10 publications
6
26
0
1
Order By: Relevance
“…5 Three studies looking specifically at CD operative times showed that surgeon experience does influence operative times, though with conflicting results between studies. 6,7,10 Our results are in agreement with those described by Doherty et al 7 and Wong et al 10 with training surgeons increasing CD operative times by 5–14 minutes depending on their level of training. In contrast, Wilson et al 6 showed decreased operative time when CD was performed by residents or fellows compared to attendings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 Three studies looking specifically at CD operative times showed that surgeon experience does influence operative times, though with conflicting results between studies. 6,7,10 Our results are in agreement with those described by Doherty et al 7 and Wong et al 10 with training surgeons increasing CD operative times by 5–14 minutes depending on their level of training. In contrast, Wilson et al 6 showed decreased operative time when CD was performed by residents or fellows compared to attendings.…”
Section: Discussionsupporting
confidence: 92%
“…Factors affecting CD times, such as the surgeon’s experience, the patient’s BMI and race/ethnicity, the fetal gestational age, a history of a previous CD, concurrent bilateral tubal ligation, previous abdominal surgery other than CD, the CD indication and urgency, and the type of uterine incision (vertical versus low transverse), have been described 4,6,7 but differences in practices exist that make such results only moderately generalizable. In this single-center study, our primary aim was to determine institutional operative times for first, second, third and fourth or more CDs at our institution, which is a tertiary/quaternary care urban academic medical center.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged operative times have been associated with increased blood loss, infectious morbidity, and surgical complications. [7][8][9] Our study does not demonstrate causation but highlights an association of longer cesarean operative times in the first 8 years after implementation of the 80-hour workweek. Interpreting the causes and implications of these trends is challenging, given the multitude of factors that may potentially impact surgical time.…”
Section: Discussionmentioning
confidence: 99%
“…As caesarean section is a commonly used procedure and the clinical characteristics of subjects in the two groups were not significantly different, there was no significant difference in opertaton time between the two groups. In a retrospective study, Doherty et al [25] reported the operation time of caesarean section was significantly related to the characteristics of the patients, including age, BMI, prior caesarean section and experience and skill of operators. Moreover, they also found that operation time was related to uterine incision.…”
Section: Discussionmentioning
confidence: 98%